2010
DOI: 10.1158/0008-5472.can-09-4120
|View full text |Cite
|
Sign up to set email alerts
|

FOXC1 Is a Potential Prognostic Biomarker with Functional Significance in Basal-like Breast Cancer

Abstract: Gene expression signatures for a basal-like breast cancer (BLBC) subtype have been associated with poor clinical outcomes, but a molecular basis for this disease remains unclear. Here, we report overexpression of the transcription factor FOXC1 as a consistent feature of BLBC compared with other molecular subtypes of breast cancer. Elevated FOXC1 expression predicted poor overall survival in BLBC (P = 0.0001), independently of other clinicopathologic prognostic factors including lymph node status, along with a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
213
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 204 publications
(233 citation statements)
references
References 25 publications
18
213
0
Order By: Relevance
“…These findings implicate BRCA1 and GATA3 corepress basal-like breast cancer genes D Tkocz et al FOXC1 as an important mediator of a number of aggressive traits associated with BLBCs and may offer opportunities to develop strategies to overcome drug resistance in this aggressive breast cancer subtype. FOXC1 has been previously identified as a poor prognostic indicator in BLBCs (Ray et al, 2010) and correlated with poor overall survival in BLBC independent of other clinicopathological prognostic factors including lymph node status. The FOXC1 gene has also been reported to be hypomethylated in CD44-positive breast cancer cells and was shown to induce a progenitor-like phenotype in differentiated mammary epithelial cells (Bloushtain-Qimron et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings implicate BRCA1 and GATA3 corepress basal-like breast cancer genes D Tkocz et al FOXC1 as an important mediator of a number of aggressive traits associated with BLBCs and may offer opportunities to develop strategies to overcome drug resistance in this aggressive breast cancer subtype. FOXC1 has been previously identified as a poor prognostic indicator in BLBCs (Ray et al, 2010) and correlated with poor overall survival in BLBC independent of other clinicopathological prognostic factors including lymph node status. The FOXC1 gene has also been reported to be hypomethylated in CD44-positive breast cancer cells and was shown to induce a progenitor-like phenotype in differentiated mammary epithelial cells (Bloushtain-Qimron et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…FOXC1-implications for chemotherapy responses, EMT and breast differentiation FOXC1 expression correlates with worse overall survival in BLBC patients and has been shown to have important roles in epithelial-to-mesenchymal transition (Ray et al, 2010;Taube et al, 2010). Whilst loss of normal BRCA1 function may be a driving event in the emergence of BLBCs, the heterogeneous nature of this poorly defined subtype and the lack of sporadic BRCA1 mutations would suggest that BRCA1 dysfunction is unlikely to be consistent across all BLBCs.…”
Section: Brca1 Interacts With and Requires Gata3 To Repress Foxc1mentioning
confidence: 99%
See 1 more Smart Citation
“…23 Recently, Ray et al reported that FOXC1 overexpression is a consistent feature of early invasive breast cancer and basal-like breast cancer. 26 Muggerud et al also reported that FOXC1 knockdown suppressed cell proliferation, migration and invasion in breast cancer cells. 27 Taube et al reported that FOXC1 involvement in an epithelial to mesenchymal transition signature that correlates strongly with poor outcomes in breast cancer.…”
Section: Cancer Cell Biologymentioning
confidence: 96%
“…Most of these tumors are infiltrating ductal tumors with solid growth pattern, aggressive clinical behavior, and high rate of metastasis to the brain and lung. Unlike other BC subtypes, there seems to be no correlation between tumor size and lymph node metastasis in BLBC [1, 11,49]. The most common histological type of BLBC is invasive ductal carcinoma, however BLBC also involves some unique histological types including invasive lobular, medullary, metaplastic, myoepithelial, neuroendocine, apocrine, adenpid cystic, and secretory breast carcinoma [50].…”
Section: Clinicopathological Features Of Blbcmentioning
confidence: 99%